Game-Based Learning Model with Baamboozle Media Based on Artificial Intelligence Increases Student Engagement and Learning Outcomes - Mega Ega Wardani; Siti Maryatul Kiptiyah (Jurnal Ilmiah Sekolah Dasar, 2024)
The rise of students who have low learning outcomes and student engagement. Low mathematics learning outcomes are caused by models or learning media that are unsuitable for use in learning. This research aims to test the effectiveness of using the Game-Based Learning learning model with the assistance of Baamboozle media on Student Engagement and student learning outcomes. The research method used in this research is a quasi-experiment with a one-group pre-test and post-test design. The total sample for this research was 27 third-grade elementary school students. Data collection methods in this research are observation, questionnaires, and tests. The instrument used to collect data is test questions. Data analysis techniques use inferential statistics. The research results, namely the post-test results, show that all students completed the KKM. The t-test results showed differences in the pre-test and post-test after using the Game-Based Learning learning model with Baamboozle media. The results of questionnaires and teacher observations show that Student Engagement has increased. It was concluded that the Game-Based Learning learning model using Baamboozle media effectively improved learning outcomes and Student Engagement in mathematics content.